Centella asiatica and its caffeoylquinic acid and triterpene constituents increase dendritic arborization of mouse primary hippocampal neurons and improve age-related locomotion deficits in Drosophila - Rowe, Karon; Gray, Nora E.; Zweig, Jonathan A.; Law, Alexander; Techen, Natascha; Maier, Claudia S.; Soumyanath, Amala; Kretzschmar, Doris (Frontiers in Aging, 2024)
IntroductionCentella asiatica (CA) is known in Ayurvedic medicine as a rejuvenating herb with particular benefits in the nervous system. Two groups of specialized metabolites found in CA and purported to contribute to its beneficial effects are triterpenes (TTs) and caffeoylquinic acids (CQAs). In order to evaluate the role and interactions of TTs and CQAs in the effects of CA, we examined the neurotrophic effects of a water extract of CA (CAW) and combinations of its TT and CQA components in mouse primary hippocampal neurons in vitro and in Drosophila melanogaster flies in vivo.MethodsPrimary hippocampal neurons were isolated from mouse embryos and exposed in vitro for 5 days to CAW (50 μg/mL), mixtures of TTs, CQAs or TT + CQA components or to 4 TTs or 8 individual CQA compounds of CAW. Dendritic arborization was evaluated using Sholl analysis. Drosophila flies were aged to 28 days and treated for 2 weeks with CAW (10 mg/mL) in the food, mixtures of TTs, CQAs or TT + CQA and individual TT and CQA compounds. TTs and CQAs were tested at concentrations matching their levels in the CAW treatment used. After 2 weeks of treatment, Drosophila aged 42 days were evaluated for phototaxis responses.ResultsIn mouse primary hippocampal neurons, CAW (50 μg/mL), the TT mix, CQA mix, all individual TTs and most CQAs significantly increased dendritic arborization to greater than control levels. However, the TT + CQA combination significantly decreased dendritic arborization. In Drosophila, a marked age-related decline in fast phototaxis response was observed in both males and females over a 60 days period. However, resilience to this decline was afforded in both male and female flies by treatment from 28 days onwards with CAW (10 mg/mL), or equivalent concentrations of mixed TTs, mixed CQAs and a TT + CQA mix. Of all the individual compounds, only 1,5-diCQA slowed age-related decline in phototaxis in male and female flies.DiscussionThis study confirmed the ability of CAW to increase mouse neuronal dendritic arborization, and to provide resilience to age-related neurological decline in Drosophila. The TT and CQA components both contribute to these effects but do not have a synergistic effect. While individual TTs and most individual CQAs increased dendritic arborization at CAW equivalent concentrations, in the Drosophila model, only 1,5-diCQA was able to slow down the age-related decline in phototaxis. This suggests that combinations (or potentially higher concentrations) of the other compounds are needed to provide resilience in this model.